Handbook of vocational education and training : developments in the changing world of work. Volume 2 - McGrath, Simon [Herausgeber]; Mulder, Martin [Herausgeber]; Papier, Joy [Herausgeber]; Suart, Rebecca [Herausgeber] (Springer, 2019)
"This handbook brings together and promotes research on the area of vocational education and training (VET). It analyzes current and future economic and labor market trends and relates these to likely implications for vocational education and training. It questions how VET engages with the growing power of human development approaches and with the sustainable development agenda. Equity and inclusion are discussed in a range of ways by the authors and the consideration of the construction of these terms is an important element of the handbook. It further addresses both the overall notion of system reform, at different scales, and what is known about particular technologies of systems reform across a variety of settings. Vocational learning and VET teacher/trainer education are discussed from a comparative perspective. National and comparative experiences are also shared on questions of equity and efficiency in funding in terms of those that fund and are funded, and for a range of funding methodologies. As well as reviewing existing gaps, this handbook is looking forward in identifying promising new directions in research and environment. Volume two covers the areas Vocational learning; Competence and excellence; Measuring learning and instructional performance; Supporting learners; VET teacher/trainer education." (Publisher, BIBB-Doku)
Keywords: S System beruflicher Bildung; G 1.2 Arbeitsmarkt; L 6.3.1 Diagnose- & Messinstrumente; I 2.3.4 Asien; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; I 2.3.1 Afrika; I 2.3.5 Australien, Ozeanien; I 2.3.2 Nordamerika; I 2.3.3 Lateinamerika; Berufsbildung; Berufsbildungssystem; Arbeitswelt; Qualifikationswandel; Kompetenzentwicklung; Kompetenzfeststellung; Lernen am Arbeitsplatz; Lebenslanges Lernen; Selbstkompetenz; Internationaler Vergleich; Älterer Arbeitnehmer; China; Großbritannien; Schweiz; Ungarn; Südafrika; Australien; Amerika; Mexiko; Simbabwe